Railroad audits: Some arrived ahead of schedule - Feeney, K. (Accounting Historians Journal, 2013)
Through 1975, the shareholder annual reports of publicly-owned U.S. railroads were exempt from the Securities and Exchange Commission’s accounting regulations, audit and disclosure rules because railroads were common carriers subject to the rules and regulations of the Interstate Commerce Commission (ICC). Pub-liclyowned Class railroads voluntary began to away from ICC-type towards GAAP-type accounting and disclosures in their shareholder reports just after World War II.1 This paper reviews early industry practices with respect to internal and external audits. Using a sample of major Class I railroads from 1946 to 1975, the paper shows: the extent to which certain railroads voluntarily presented audited finan-cial statements before being required, the extent to which particular CPA firms were involved with the railroad industry, and the types of audit reports that issued to these railroads during this period. © 2016, Academy of Accounting Historians. All rights reserved.
3 citations (Crossref) [2023-10-31]
Keywords: dept.acc